1994
DOI: 10.1164/ajrccm.149.6.8004297
|View full text |Cite
|
Sign up to set email alerts
|

Postallergen inhaled budesonide reduces late asthmatic response and inhibits the associated increase of airway responsiveness to methacholine in asthmatics.

Abstract: To determine whether inhaled budesonide given after allergen inhalation challenge inhibits the late asthmatic response (LAR) and/or the associated increase of airway responsiveness to methacholine, we performed a double-blind randomized cross-over study in 12 adult asthmatics (eight male, four female; mean age, 20.3 yr; range, 18 to 29 yr) sensitized to Dermatophagoides pteronyssinus (DP) previously shown to develop early and late asthmatic response to allergen challenge with DP. On different days each subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 25 publications
(17 reference statements)
3
29
0
1
Order By: Relevance
“…Dosedependent inhibition of LAR induced by LMW agents has also been documented after prolonged treatment with inhaled and oral steroids [144,[169][170][171]. When administered after EAR, inhaled steroids are effective in reducing the LAR [154,155], but are only slightly effective in inhibiting the increase in NSBHR [154,155]. This is consistent with the observation that an increase in NSBHR can develop as soon as 1-3 h after the early component of DAR.…”
Section: Effect On Larsupporting
confidence: 66%
“…Dosedependent inhibition of LAR induced by LMW agents has also been documented after prolonged treatment with inhaled and oral steroids [144,[169][170][171]. When administered after EAR, inhaled steroids are effective in reducing the LAR [154,155], but are only slightly effective in inhibiting the increase in NSBHR [154,155]. This is consistent with the observation that an increase in NSBHR can develop as soon as 1-3 h after the early component of DAR.…”
Section: Effect On Larsupporting
confidence: 66%
“…On the other hand, the more balanced lipophilic/hydrophilic characteristics of budesonide may explain its higher efficacy in terms of rapid onset of action, in part due to the strong nongenomic effects of budesonide. Several in vitro and in vivo experimental studies have confirmed that an anti-inflammatory effect of budesonide may be detected a few hours after administration [11,12].…”
Section: Pharmacology Of Inhaled Corticosteroidsmentioning
confidence: 91%
“…Studies on an effect of fluticasone or budesonide compared with montelukast revealed a positive impact of all three substances on an early asthmatic response, with steroids being superior in improving bronchial hyperresponsiveness [26,27]. Additionally, a positive impact of inhaled corticosteroids on the late asthmatic response could also be demonstrated [28]. Keeping the side-effects of steroids in mind, the goal of the present study was to further investigate montelukast as an add-on option to b-mimetics in mild bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%